Implementasi Program Pendampingan Manajemen dalam Rangka Meningkatkan Kualitas Pengelolaan Industri Mikro dan Kecil Batik di Kota Mojokerto - Dwi Bhakti Iriantini; Wahyudiono Wahyudiono; Santirianingrum Soebandhi; Yuda Prawira; Nisrina Dwi Nur Raniah (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This community service program aims to provide management assistance to micro and small batik industries in optimizing digital platform and social media-based marketing. This allows these micro and small batik industry players to reach a wider network and ensure their business sustainability in the future after the pandemic. This community service program uses a qualitative descriptive approach, which aims to capture the real-world conditions related to the management of batik industry players in Mojokerto. This mentoring program was attended by micro and small batik industry players, primarily small and craft industries, including 10 batik artisans and industry managers residing in Mojokerto. The mentoring method was implemented through four stages: a) identifying mentoring needs for micro and small batik industry players, b) selecting management literacy priorities, c) designing a management literacy mentoring program, and d) implementing the management mentoring program for micro and small batik industries. The management mentoring program indicates that micro and small batik industry players require ongoing marketing and business development management mentoring. After entering the COVID-19 pandemic, batik industry players in Mojokerto have not been able to recover to pre-COVID-19 levels in 2019. The management mentoring program includes four stages: a) delivering material on the role of management, business sustainability, business problems, and formulating solutions; b) identifying relevant management problems discussed in a focus group discussion; c) mentoring on marketing aspects and optimizing the role of cooperatives within batik industry groups; d) mentoring on business sustainability management through digital business optimization. Through this structured management mentoring program, micro and small batik industry players will be able to improve their management and business management.